2012
DOI: 10.2478/s11756-012-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of permethrin contamination on nematode density and diversity: A microcosm study on benthic meiofauna from a Mediterranean coastal lagoon

Abstract: A microcosm experiment was used to examine the response of nematode in terms of density and diversity at different levels of permethrin contamination. The sediments were contaminated with three permethrin concentrations [P1: low (5 mg kg −1 ), P2: medium (25 mg kg −1 ) and P3: high (250 mg kg −1 )] and the effects were evaluated after 30 days. The results from univariate and multivariate analyses showed significant differences between nematode assemblages from uncontaminated control and those from permethrin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Nematodes numbers in the soil (treated with organic phosphate or carbamate) were also reduced, and likewise for some pesticides applied to the grassland without mixing into the soil reducing nematode numbers by 48% (Römbke et al, 2009). Additionally, Soltani et al (2012) reported that the total number of nematodes, species richness and number of species fell in all contaminated microcosm where permethrin applied.…”
Section: Resultsmentioning
confidence: 99%
“…Nematodes numbers in the soil (treated with organic phosphate or carbamate) were also reduced, and likewise for some pesticides applied to the grassland without mixing into the soil reducing nematode numbers by 48% (Römbke et al, 2009). Additionally, Soltani et al (2012) reported that the total number of nematodes, species richness and number of species fell in all contaminated microcosm where permethrin applied.…”
Section: Resultsmentioning
confidence: 99%
“…Impact of pesticides has also been demonstrated on free-living marine nematode assemblages. Several studies on the impact of pesticides on a free-living marine nematode community were performed in microcosm experiments showing controversial effects (Boufahja et al 2011;Soltani et al 2012). The total nematode abundance, diversity (Shannon-Wiener index H′), and species richness were reduced in all treatments compared to control (Soltani et al 2012) while the abundance of nematodes in all pesticide concentrations significantly exceeded those in the control (Boufahja et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the impact of pesticides on a free-living marine nematode community were performed in microcosm experiments showing controversial effects (Boufahja et al 2011;Soltani et al 2012). The total nematode abundance, diversity (Shannon-Wiener index H′), and species richness were reduced in all treatments compared to control (Soltani et al 2012) while the abundance of nematodes in all pesticide concentrations significantly exceeded those in the control (Boufahja et al 2011). The species of free-living marine nematode Pselionema sp., Prochromadorella neapolitana, Spiriniager lachi, and Daptonema trabeculosum were found sensitive to permethrin, while the species Trichotheristus mirabilis, Xyala striata, Araeolaimus bioculatus, Calomicrolaimus honestus, Oncholaimus campylocercoides, and Theristus pertenuis were found resistant and proliferated (Boufahja et al 2011;Soltani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of the synthetic pyrethroids to control of wireworm and mirids offers protection to above and below ground herbivorous damage, however, their impact on nematodes is negligible [5,15]. This assumption is based on the facts that no deleterious effects from synthetic pyrethroids have been found on entomophathogenic nematodes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is based on the facts that no deleterious effects from synthetic pyrethroids have been found on entomophathogenic nematodes [16][17][18]. However, when pyrethroids were introduced to aquatic systems nematodes flourished [19], although Daptonema trabeculosum was found to be sensitive to permethrin [15].…”
Section: Introductionmentioning
confidence: 99%